The Impacts of Digital Leadership and Work Motivation on the Organizational Commitment of State Middle School Teachers - Aulia, Yenni; Syahril; Anisah; Susanti, Lusi (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to reveal the influence of digital leadership and work motivation on organizational commitment. This research was quantitative and was of a correlational associative type. The population in this research was all the 520 civil servant teachers who taught at State Middle Schools in West Pasaman Regency. In comparison, the sample in this research was 156 teachers with the Cochran formula with an error rate of 10% with the cluster random sampling technique. Data was collected using a Likert scale model questionnaire, which was tested for validity and reliability. The research data were processed using SPSS version 26 after carrying out prerequisite tests consisting of normality tests, linearity tests, multicollinearity tests, regression coefficient significance tests, and correlational tests. The results of data analysis show that (1) digital leadership influences teacher organizational commitment, (2) work motivation influences teacher organizational commitment, and (3) digital leadership and work motivation have the same effect on teacher organizational commitment.